“evaluacion de la temperatura de calcinación y el tamaño de partícula de valvas de concha de abanico sobre el porcentaje de remoción de cromo trivalente en soluciones acuosas artificiales de cr3+ mediante un proceso de precipitación” - Moreno Grijalba, Diego André (2016)
In this research it was evaluated the influence of the calcination temperature and particle size of the scallop shell, on the percentage removal of trivalent chromium in aqueous solutions artificial cromo3 + was assessed by a precipitation process For research 8 kg of scallop shell was obtained, the company obtained Aquaculture and Fisheries Group Acuapesca S.A.C. Located in the Panamericana Norte Highway Km. 383.3 in Casma. The collection of these samples was made randomly. Which they were washed with water and detergent that removed all impurities. It was triturated using a clap stone and then ground by a ball mill, where the particle size was reduced according to ASTM EN ° 100 (≤0.149mm,> 0.074mm), No. 200 (≤0.074mm, > 0.044mm) and No. 325 (≤0.044mm), screened with stainless steel mesh and stored in airtight bags. To test removal 8 liters obtained an artificial solution of trivalent chromium (Cr3+) to 10,000 ppm prepared in General Chemistry Laboratory of the National University of Trujillo, this was the initial concentration. For this analysis was used 250mL of chromium solution with 5 grams of each leaflet triturated with different sizes. By a magnetic stirrer rapid mixing of 10 minutes at 400 rpm and a slow mix of 30 minutes at 120 rpm was carried out, then the solution was left for 24 hours hermetically sealed with adhesive paper. For the analysis of final concentration, 100 mL of each test was obtained and labeled in plastic containers and delivered to the Laboratory of Community Services and Research (LASACI). For the characterization of the scallop shell, an essay by TGA and DTA was performed using the computer Setsys Evolution TG in Polymeric Materials Laboratory of the National University of Trujillo. The results of analyzing the leaflet by TGA and DTA, showed the composition of the heat-treated off the chromium solution valve, 600 ° C interacted calcium carbonate with Cr3+ and 800 ° C and 1000 ° C, interacted oxide versus calcium metal. This explained the variation in the percentage of removal at 600 ° C of almost 45% compared to almost 90% to calcining at 800 ° C and 1000 ° C. This is explained as follows, that both samples calcined (600 ° C and 1000 ° C) raise the pH of the solution, ie they release OH- ions which favors the precipitation of chromium hydroxide on the surface of the valve . Import particle size was very small, it explained that smaller larger surface area of the valve that interacted with Cr3+. The conclusion of the study was that the calcination at 1000 ° C with the smaller particle size decreases greater% chromium. Also it demonstrated with the analysis of variance (ANOVA), independent variables that significantly affect the removal of Cr3 +. Keywords: Chrome, tannery, scallop shell, calcination